Activation of auditory cortex during silent lipreading. - Calvert, G; Bullmore, E; Brammer, M; Campbell, R; Williams, S; McGuire, P; Woodruff, P; Iversen, S; David, A (1997)
Watching a speaker's lips during face-to-face conversation (lipreading) markedly improves speech perception, particularly in noisy conditions. With functional magnetic resonance imaging it was found that these linguistic visual cues are sufficient to activate auditory cortex in normal hearing individuals in the absence of auditory speech sounds. Two further experiments suggest that these auditory cortical areas are not engaged when an individual is viewing nonlinguistic facial movements but appear to be activated by silent meaningless speechlike movements (pseudospeech). This supports psycholinguistic evidence that seen speech influences the perception of heard speech at a prelexical stage.